Conserved C-Terminal Threonine of Hepatitis C Virus NS3 Regulates Autoproteolysis and Prevents Product Inhibition - Wang, Wenyan (American Society for Microbiology, 2004)
Inspection of over 250 hepatitis C virus (HCV) genome sequences shows that a threonine is strictly conserved at the P1 position in the NS3-NS4A (NS3-4A) autoproteolysis junction, while a cysteine is maintained as the P1 residue in all of the putative trans cleavage sites (NS4A-4B, NS4B-5A, and NS5A-5B). To understand why T631 is conserved at the NS3-4A junction of HCV, a series of in vitro transcription-translation studies were carried out using wild-type and mutant (T631C) NS3-4A constructs bearing native, truncated, and mutant NS4A segments. The autocleavage of the wild-type junction was found to be dependent on the presence of the central cofactor domain of NS4A (residues 21 to 34). In contrast, all NS3-4A T631C mutant proteins underwent self-cleavage even in the absence of the cofactor. Subgenomic replicons derived from the Con1 strain of HCV and bearing the T631C mutation showed reduced levels of colony formation in transfection studies. Similarly, replicons derived from a second genotype 1b virus, HCV-N, demonstrated a comparable reduction in replication efficiency in transient-transfection assays. These data suggest that the threonine is conserved at position 631 because it serves two functions: (i) to slow processing at the NS3-4A cleavage site, ensuring proper intercalation of the NS4A cofactor with NS3 prior to polyprotein scission, and (ii) to prevent subsequent product inhibition by the NS3 C terminus.